2014
DOI: 10.1007/s00229-014-0721-7
|View full text |Cite
|
Sign up to set email alerts
|

Two torsion in the Brauer group of a hyperelliptic curve

Abstract: Abstract. We construct unramified central simple algebras representing 2-torsion classes in the Brauer group of a hyperelliptic curve, and show that every 2-torsion class can be constructed this way when the curve has a rational Weierstrass point or when the base field is C 1 . In general, we show that a large (but in general proper) subgroup of the 2-torsion classes are given by the construction. Examples demonstrating applications to the arithmetic of hyperelliptic curves defined over number fields are given. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…For any ∈ L × , let A be the L(x)-algebra obtained by adjoining anticommuting square roots of x − θ and to L(x). The corestriction A := Cor L(x)/K(x) (A ) is a tensor product of quaternion algebras over K(x) which can be explicitly computed using Rosset-Tate reciprocity (see [11,Proposition 3.1]). In [11] it is shown that, under suitable conditions on the norm of , the algebra A pulls back to an unramified central simple k(X)-algebra A := A ⊗ K(x) k(X).…”
Section: Statement Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For any ∈ L × , let A be the L(x)-algebra obtained by adjoining anticommuting square roots of x − θ and to L(x). The corestriction A := Cor L(x)/K(x) (A ) is a tensor product of quaternion algebras over K(x) which can be explicitly computed using Rosset-Tate reciprocity (see [11,Proposition 3.1]). In [11] it is shown that, under suitable conditions on the norm of , the algebra A pulls back to an unramified central simple k(X)-algebra A := A ⊗ K(x) k(X).…”
Section: Statement Of the Resultsmentioning
confidence: 99%
“…In general there exist Brauer-like torsors of period 2 under J which are not of the form V . For example, see [11,Proposition 5.1 and Remark 5.4]. We also note that the hypothesis Br 0 (X/K) = 0 is satisfied quite frequently, as suggested by the following lemma.…”
Section: Even Hyperelliptic Curvesmentioning
confidence: 89%
See 1 more Smart Citation
“…in finding an explicit representative for [the nontrivial] Brauer class of [X a ]." Recent work of Creutz and the last author [CV14a,CV14b], and Ingalls, Obus, Ozman, and the last author [IOOV] makes this problem more tractable. Building on techniques from [CV14a, CV14b, IOOV], we prove:…”
Section: Introductionmentioning
confidence: 99%
“…v := ψ(1 : −6 : 1 + i : −6 − i : 2 √ 4255 − 4160i). The point Q v lies over t = 36 and B t consists of 2 F v -points R 1 and R 2 and one quadratic point R; they have s values 19Since these points are unramified in B → P 1 and are away from the support of ℓ and α, the cocycle description of γ ′ (ℓ) in[CV, Lem. 3.5]shows thatA(Q v ) = (ℓ(−2), 25) 2 + (ℓ(−10), 35) 2 + γ ′ (ℓ)(Q v ) = (ℓ(10), 35) 2 + Cor Q 2 (i, √ 109)/Q 2 (i) ((x(Q v ) − α(R), ℓ(R)) 2 ) + 2 j=1 (x(Q v ) − α(R j ), ℓ(R j )) 2 .…”
mentioning
confidence: 99%